Dr. Mahathir : amanah & visi - Hambali Abdul Latiff (Selangor : Penerbitan Wadah Karya, 2001)
On the management and role of the United Malaysia National Organisation in Malaysia's politics and government ; speeches.
Includes bibliographical references.
Koleksi sumbangan Tun Ahmad Sarji Abdul Hamid.
Keywords: Mahathir Mohamad, -- Tun, -- 1925-; United Malays National Organisation; Prime ministers -- Malaysia; Malaysia -- Politics and government; Malaysia -- History